2018
DOI: 10.1111/flan.12356
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dyad type on collaboration: Interactions among heritage and second language learners

Abstract: This study investigated the dynamics between matched heritage language learner (HLL) dyads, second language learner (L2L) dyads, and mixed HLL‐L2L dyads in the Spanish L2 classroom. Data come from 15‐minute video recordings of 16 dyads, including four HLL–HLL, four L2L–L2L, and eight HLL–L2L dyads that were collected during collaborative writing activities in level 1 and 2 classes at a community college in southern California. Dyads’ interactions were analyzed and then categorized according to the predominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Spanish HLLs tended to take on the role of "expert" (Blake & Zyzik, 2003;Bowles, 2011;Bowles et al, 2014;Tocaimaza-Hatch, 2015;Valentín-Rivera, 2016;Walls, 2018). However, HLLs' "expertise" was not absolute.…”
Section: Heritage Language Learners and Peer Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spanish HLLs tended to take on the role of "expert" (Blake & Zyzik, 2003;Bowles, 2011;Bowles et al, 2014;Tocaimaza-Hatch, 2015;Valentín-Rivera, 2016;Walls, 2018). However, HLLs' "expertise" was not absolute.…”
Section: Heritage Language Learners and Peer Interactionmentioning
confidence: 99%
“…This research explored interactional patterns that emerged when HLLs worked in “mixed dyads” (i.e., HLL‐L2L) and compared them to “matched dyads” (i.e., HLL‐HLL or L2L‐L2L). Analyzing the predominant characteristics of 16 dyads (eight matched, eight mixed), Walls (2018) established that matched dyads were more likely to engage in collaborative patterns of interaction than those in mixed pairs. In mixed dyads, Spanish HLLs tended to take on the role of “expert” (Blake & Zyzik, 2003; Bowles, 2011; Bowles et al, 2014; Tocaimaza‐Hatch, 2015; Valentín‐Rivera, 2016; Walls, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given these similarities and differences between L2 and HL learners, along with the fact that both types of learners are often enrolled in the same language courses, a growing body of research has started to examine the characteristics and the outcomes of L2-HL dyadic interaction (Blake and Zyzik 2003;Bowles 2011a;Bowles et al 2014;Fernández-Dobao 2020;Henshaw 2015;Torres and Cung 2019;Walls 2018). The first researchers to investigate L2-HL interactions, Blake and Zyzik (2003), examined text-based synchronous computer-mediated communication exchanges between 11 pairs of L2 and HL learners and it was found that in 75% of the episodes of negotiation, the HL learner aided the L2 learner, and out of a total of 30 episodes, 24 involved the selection of vocabulary.…”
Section: Research On L2-hl Interactionmentioning
confidence: 99%
“…As also seen in Blake and Zyzik (2003), most of the focus‐on‐form and language‐related episodes identified were triggered by L2 learners and solved by their HL partners. Other studies have analyzed mixed interactions in the context of a service‐learning course (Tocaimaza‐Hatch & Walls, 2016), or by focusing on more specific aspects such as pair dynamics (Walls, 2018) or engagement with written corrective feedback (Valentín‐Rivera, 2016). All of them observed advantages, as well as disadvantages, of mixing HL and L2 learners.…”
Section: Introductionmentioning
confidence: 99%
“…L2 learners can benefit from HL learners' vocabulary knowledge, native‐like pronunciation, and fluent conversational speech; HL learners can take advantage of L2 learners' metalinguistic knowledge and writing abilities; and both groups can learn from each other's perspectives on culture. Several studies have investigated the potential benefits of combining HL and L2 learners in a single classroom by analyzing the nature of their task‐based interactions (e.g., Blake & Zyzik, 2003; Bowles et al, 2014; Henshaw, 2015; Walls, 2018). These studies will be discussed in the next section.…”
Section: Introductionmentioning
confidence: 99%